Marksian Aesthetics (Journal of the College of Education for Women, 2019)
the Aesthetics Approach For Marx is Arts goes is live With his Material Philosophy.But that does not mean that, the aesthetic for Marx is equal with, the aesthetic in Art in itsimportance even if there are complicated relations between the two . There for Marx consideredthat for each human practiced material activity. There is an aesthetic aspect and this what makesArts a distinguished form of social knowledge .The aesthetic here is a dialectic unit used toreflect life and value.